A Rare Case of Gastrointestinal Stromal Tumor with a Liver Metastasis Infiltrating the Inferior Vena Cava and Extending to the Right Atrium with an Early Recurrence after Surgical Extraction - Dimitrios Siamkouris; Marc Schloesser; Amr Yousef; Elmar Offers (Case Reports in Cardiology)
Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors of the gastrointestinal tract. The major cause of GIST is the presence of an abnormal form of tyrosine protein kinase (KIT) protein also known as CD117, which causes uncontrollable growth of the gastrointestinal cells. Most studies report incidences between 10 and 15 cases of GISTs per million. Metastases to the liver and peritoneum are the most frequent. We report a case of advanced GIST with a liver metastasis infiltrating the inferior vena cava (IVC) and extending to the right atrium in the form of a large, floating, isolated intracardiac liver metastasis with diastolic prolapsing through the tricuspid valve. This is a very rare manifestation. One week after heart surgery and removal of a 5×6 cm tumor mass from the right atrium and the IVC, echocardiography depicted an early recurrence.